2004
DOI: 10.1086/374720
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward Implementation of a Second-Dose Measles Immunization Requirement for All Schoolchildren in the United States

Abstract: In 1998, the Advisory Committee on Immunization Practices and the American Academy of Pediatrics recommended that states ensure that all children in grades kindergarten through 12 receive 2 doses of measles-mumps-rubella (MMR) vaccine by 2001. In 2000, the National Immunization Program surveyed states, the District of Columbia, and United States territories, commonwealths, and protectorates to assess progress toward this goal. Almost all respondents (53 [98%] of 54) reported a second-dose requirement for entry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 10 publications
(9 reference statements)
1
17
0
Order By: Relevance
“…In addition, our findings are further supported by national coverage surveys since 1995 that show high (у90%) vaccine coverage among preschool-aged children at 19-35 months of age and surveillance data that show sustained interruption of indigenous measles transmission [1,21]. Currently, immunity among schoolchildren and young adults is even higher than during the study period, because a 2-dose measles vaccination requirement is now more widely implemented for schoolchildren, college students, and health care workers [8,22].…”
Section: Discussionsupporting
confidence: 68%
“…In addition, our findings are further supported by national coverage surveys since 1995 that show high (у90%) vaccine coverage among preschool-aged children at 19-35 months of age and surveillance data that show sustained interruption of indigenous measles transmission [1,21]. Currently, immunity among schoolchildren and young adults is even higher than during the study period, because a 2-dose measles vaccination requirement is now more widely implemented for schoolchildren, college students, and health care workers [8,22].…”
Section: Discussionsupporting
confidence: 68%
“…Implementation and enforcement of school entry requirements for other vaccines, such as the MMR vaccine, has resulted in vaccination coverage among school-aged children of 97%-99%, providing high levels of protection against vaccine-preventable diseases in these settings with a high risk of transmission [2]. States are encouraged to implement varicella vaccination entry requirements for multiple school levels simultaneously, to ensure coverage of all grade levels as rapidly as possible.…”
Section: Resultsmentioning
confidence: 99%
“…Imple-P p .002 mentation of day care and school entry requirements for varicella vaccination is an important strategy for achieving and maintaining high vaccination coverage among preschool-and school-aged children in the United States. The newly adopted vaccine policy recommendation of 2 doses of varicella vaccine for all school-aged children should be incorporated into the states' school entry requirements.For 1100 years in the United States, vaccination requirements for day care and school entry have been an effective strategy in the promotion of increases in vaccination coverage and decreases in the incidence of vaccine-preventable diseases [1][2][3][4][5][6]. In the 1970s, Alaska and California demonstrated that school entry vaccination requirements, combined with the exclusion of nonvaccinated students during measles outbreaks, were effective strategies in controlling measles outbreaks [3].…”
mentioning
confidence: 99%
“…72 After steady progress in the 1980s, a major resurgence of measles began in 1989 in children and adolescents. 73 With the recommendation for a second dose of measles vaccine in 1989 2 and passage and enforcement of school-entry requirements for second-dose vaccination, 74 indigenous transmission has been eliminated. 75 At the same time, rubella and congenital rubella syndrome were eliminated in this country.…”
Section: Measles-mumps-rubellamentioning
confidence: 99%